Morphometric analysis and land use-occupation in the Campestre creek watershed in the city of Lins, São Paulo State, Brazil. - Mercado, Leticia Sales; Lima, César Gustavo da Rocha; di Lollo, José Augusto (Periódico Eletrônico Fórum Ambiental da Alta Paulista, 2023)
The increased demand for natural resources, economic growth and graph growth can influence the reduction of individual land use coverage, which makes water infiltration difficult. The objective was to evaluate, through the morphometric parameters and land-use occupation, the flooding susceptibility in the Campestre creek watershed. An analysis of the morphometric indexes was performed with the help of the tools presented in the SPRING 5.4.3 software. The characteristics of land use and occupation were identified by the of classification by regions, using images from three different periods: 1990, 2005 and 2021. The satellite images used were LANDSAT 5, TM sensor and LANDSAT 8, OLI sensor, and finally, as an auxiliary project to the study, Numerical Terrain Modeling data from the SRTM Project was used, with a spatial resolution of 30 meters. The morphometric results show that the Campestre creek watershed has a circular shape and straight channels, which contributes to the classification of medium-high susceptibility to floods and inundations. There was a 13% increase in built-up areas in regions that were previously water and vegetation, from 4.2 km² to 4.87 km² in 2021. The reduction of permeable areas makes it difficult for water to infiltrate, contributing to the occurrence of floods and inundations.